Ādhunika pariprekshya meṃ Bhāratīya darśana kī prāsāṅgikat - Kumāra, Śaśiprabhā; Seminar on "Relevance of Indian Philosophy in modern context (Nāga Prakāśaka, 1993)
Contributed research papers.
"Saṃskr̥ta Vibhāga, Maitreyī Kāleja ke saujanya se."
Title on added t.p.: Relevance of Indian philosophy in modern context.
English, Hindi, and Sanskrit.
Includes bibliographical references.
Contributed research papers.
Keywords: Philosophy, Indic / Congresses. / http://id.loc.gov/authorities/subjects/sh2010106094